Kemampuan Representasi Matematis Ditinjau Dari Self Efficacy Siswa Kelas VIII Tahun Ajaran 2020/2021 - Retno Saputri Said; Sri Subarinah; Baidowi Baidowi; Sripatmi Sripatmi (Griya Journal of Mathematics Education and Application, 2021)
This study aimed to describe the mathematical representation ability in terms of self-efficacy students of grade VIII SMP Negeri 6 Mataram in academic year 2020/2021. The research method used was descriptive research with qualitative approach. The instruments used in this study were self-efficacy questionnaires, mathematical representation ability tests and interview guides. The research subjects were 31 students of grade VIII E with 22 students having high self-efficacy and 9 students having low self-efficacy. Then 3 students from each category of self-efficacy were selected to be given a test and an interview. Based on the results, the mathematical representation abilities of students who have high self-efficacy are able to present a mathematical problem in the form of images or diagrams, solve mathematical problems using mathematical equations or models and sufficiently able to use written words in solving mathematical problems. Meanwhile, the mathematical representation abilities of students who have low self-efficacy are able to present a mathematical problem in the form of a picture